Genomic landscape of a long-term surviving patient with metastatic cancer of the larynx: a case report - Bišof, Vesna; Soče, Majana; Škrtić, Anita; Seiwert, Sven; Peričić Salihović, Marijana (Frontiers in Oncology, 2025)
Head and neck squamous cell carcinoma (HNSCC) remains a major global health challenge, with limited long-term survival in the recurrent/metastatic (R/M) setting. Here, we present a rare case of a patient with metastatic laryngeal squamous cell carcinoma who survived eight years after diagnosis of metastatic disease, treated only with standard chemotherapy, metastasectomy, and palliative radiotherapy. To explore potential genomic underpinnings of this unusually favorable outcome, we performed next-generation sequencing of tumor (lymph node and lung metastases) and germline DNA. Mutations were analyzed across ten key oncogenic signaling pathways and compared with the COSMIC and OncoKB databases. Somatic mutations were found in all ten pathways, with multiple 3′ UTR variants in EIF4EBP1 and CTBP2, genes implicated in translational regulation and transcriptional repression, respectively. Germline analysis revealed 21 high-impact mutations, three of which were rare and potentially deleterious. Our findings suggest that subtle regulatory variants may contribute to favorable clinical outcomes in rare long-term survivors of R/M HNSCC. Further studies are needed to identify predictive biomarkers in this unique subgroup of patients.